원적외선 처리된 대마종자의 급성 위염 개선 효과 - 안희연; 신미래; 김민주; 정일하; 조정은; 이우락; 노성수 (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2025)
본 실험에서는 원적외선 처리된 대마종자 추출물(FH)이 HCl/에탄올로 유발된 급성 위염에 미치는 영향을 조사하였다. 실험 결과, FH를 투여한 군에서는 대조군에 비해 농도 의존적으로 위 점막 손상이 유의미하게 감소하였다. 또한, 혈청 내 ROS 수치가 감소하였고, 위 조직 내 NF-κB 활성화로 유도되는 염증 관련 인자들이 유의미하게 감소하였다. 특히, FH 200군에서는 p22phox 단백질 발현 억제를 통해 ROS를 감소시키며, 항염증 사이토카인이 유의하게 증가하였다. 이러한 결과는 FH가 급성 위염에서 ROS를 줄이고, 산화 및 염증 반응을 완화하는 데 도움이 될 수 있음을 시사하며, 향후 관련 연구에서 유망한 후보 물질로 활용될 수 있을 것으로 기대된다. Far infrared-processed hemp seed (FH) has anti-oxidant properties, but its effect on alleviating acute gastritis has not been reported. This study examined the gastric protective effects of FH in a mouse model of acute gastritis induced by 150 mM HCl/60%. After dividing the mice into five groups, the treatment groups were administered the drug (sucralfate 10 mg/kg, SC; FH 100 mg/kg, FH100; and FH 200 mg/kg, FH200). Ninety minutes later, 150 mM HCl/60% ethanol was administered to all groups except the Normal group to induce acute gastritis. Macroscopic analysis showed that the FH treatment improved gastric mucosal damage and reduced the elevated serum reactive oxygen species (ROS) levels. Western blot analysis showed that the FH treatment suppressed ROS production by regulating NADPH oxidase protein expression. In addition, FH suppressed the inflammatory responses by reducing the expression of inflammatory proteins such as iNOS, Cox-2, and pro-inflammatory cytokines, including TNF-α and IL-6, induced by NF-κB activation. On the other hand, significant increases in anti-inflammatory cytokines were observed only in the FH200 group. In conclusion, FH treatment showed significant potential in protecting and promoting the recovery of gastric tissue, suggesting that FH may serve as a promising candidate for developing therapeutic agents targeting acute gastritis. KCI Citation Count: 0